The research on work engagement: theoretical aspects and the results of researches in the company operating in the IT sector - Wójcik-Karpacz Anna (Management, 2018)
The aim of this article is to exemplify the results of researches on work engagement in the company operating in the IT sector. The research methodology includes the studies of scientific literature and the quantitative method (survey questionnaire). The sample in the study comprises 509 employees of a company operating in the IT sector. Work engagement was measured with of the original 17-item Utrecht Work Engagement Scale (UWES). Using in the research a standardized tool gives the opportunity to compare different results obtained in subsequent periods of time in the company, as well as, it can be the point of reference in the assessment of work engagement in other companies of the IT and other sectors. The results of the research show a relatively high level of work engagement in the composite aspect and its individual dimensions and subdimensions in the company operating in the IT sector. The scientific literature studies provide the managers with information on how various issues are related to the level of work engagement and on the usefulness of periodic researches in the company. However, the results of the empiric research help the managers to diagnose of the work engagement and to take more conscious decisions how to improve or maintain it on the same level. The research findings give the overview on the topic of work engagement level in a big IT company.